THE EFFECT OF TAX AVOIDANCE, INVESTMENT DECISIONS, DIVIDEND POLICY AND CAPITAL INTENSITY ON THE COMPANY'S VALUE - Dini Andari; Adhitya Putri Pratiwi (Indonesian Journal Publisher, 2026)
This study aims to empirically examine the influence of tax avoidance, investment decisions, dividend policies, and capital intensity on company value. This study uses companies included in the LQ 45 index listed on the Indonesia Stock Exchange for the period 2020-2024. The population in this study is 45 companies. This study uses secondary data with a sampling method, namely purposive sampling, selecting data that meets the criteria. There were 21 companies that were sampled with a duration of 5 years of observation, so that the total observation data was 105 data. The data in this study is quantitative data, data comes from the annual report of the LQ 45 company. The analysis technique used is multiple linear analysis, using the E-views 12 analysis tool. The results of this study show that simultaneously tax avoidance, investment decisions, dividend policies, and capital intensity affect the value of the company. Partially Tax avoidance, investment decisions, and dividend policies affect the value of the company; Meanwhile, capital intensity has no effect on the company's value.